PROJECT BASED LEARNING IN EVOKING STUDENTSâ WILLINGNESS TO CREATE BUSINESS: A CASE STUDY IN CLASS OF ENTREPRENEURSHIP - Kayyis, Rahmatika (STKIP Muhammadiyah Pringsewu, 2017)
AbstractÂ This research has a purpose to report the implementation of Project Based Learning (PBL) as a teaching method to evoke studentsâ willingness in creating business in entrepreneurship class.The research used qualitative approach which involved the case study method. In doing the project, 62 students of STKIP Muhammadiyah Pringsewu was divided into 31 pairs. The technique of collecting data by using questionaire of motivation in creating bussiness by Utoyo. The results showed that PBL evokes students willingness and creates students independency in using their talent in creating bussiness.Â Keywords: Entrepeneurship,Â Project Based Learning, Bussiness.